THE ROLE OF EMOTIONAL INTELLIGENCE AND SOCIAL ADJUSTMENT IN MARITAL SATISFACTION (World Bulletin of Social Sciences, 2025)
The study examined the impact of psychological stability of marital relationships, empathy, emotional self-control, and interpersonal communication culture on the level of family satisfaction based on empirical data. The results show that individuals with high levels of emotional intelligence and social adaptation have an advantage in maintaining mutual understanding, sympathy, and emotional stability in family life. The level of emotional intelligence and empathy is manifested as psychological mechanisms that increase marital satisfaction.